Creative Thinking Process of Prospective Teacher Students Based on Cognitive Style in Solving Contextual Problems - Endang Suprapti; Tatag Yuli Eko Siswono; Manuharawati; Armeria Wijaya (Journal of Mathematical Pedagogy (JoMP), 2024)
This study aims to explore the creative thinking processes of prospective elementary school teacher students in solving contextual mathematical problems based on their cognitive styles. Using a qualitative descriptive approach, two students were selected through purposive sampling: one with a field independent (FI) cognitive style and high self-efficacy, and the other with a field dependent (FD) cognitive style and low self-efficacy. Data were collected through task-based tests and in-depth interviews, then validated and analyzed based on the stages of creative thinking: synthesizing ideas, building ideas, planning the implementation of ideas, and implementing the ideas. The results revealed notable differences in the creative thinking processes of the two subjects. The FI student exhibited fluency, flexibility, and novelty by generating multiple correct solutions through diverse strategies. In contrast, the FD student faced challenges in synthesizing ideas, relying on a single strategy, and producing only one correct solution. These findings highlight the significant impact of cognitive style on creative mathematical thinking and underscore the importance of tailored instructional approaches to support diverse cognitive profiles.